Marketing research in consumer behavior of meat and meat products - Assanova, T. A. (Journal of Economic Research & Business Administration, 2015)
A republic of Kazakhstan traditionally is a stock-raising country, his basic production is this meat and meat products. Demand on meat and meat products in a country is high enough and with every year all increases. This market is required marketing researches with the purpose of study of behavior of consumers, namely: what meat, in what amount, in what time, at what price, what quality etc. required for complete satisfaction consumer need. For this purpose in the process of marketing research an author studied specific factors influencing on behavior of consumer, educed sources receipts of information, assisting the increase of competitiveness of meat and meat products..